Finite element modeling and updating of the composite plate structure - R. M., Yaacob; M. A. H., Hashim; M. S. M., Sani (IOP Publishing, 2019)
Composite plate structure is broadly used in engineering structures for automotive and aerospace applications. Furthermore, the problem in vibrational is one of the industries main challenges. Composite materials are frequently used in industry for weight and cost reduction to enhance mechanical properties in structural components. This research aims to execute a composite plate structure model updating procedure. Through finite element analysis (FEA) and experimental modal analysis (EMA), modal parameters such as natural frequencies, mode shapes, and damping ratios are collected. Composite plate structure is set to be free-free boundary condition and node equivalence is done in the surface plate area. Correlation is executed between these two data sets. The discrepancies in natural frequencies between FEA and EMA were reduced with the selected parameters identified to perform structure updating model using sensitivity analysis.